Perovskite microwave dielectric ceramic preparation method, system, equipment, medium and product

By exploring the physical models of grain boundary quantity, trench and phase composition and thermodynamic parameters, the undefined problem of the influence mechanism of the resonant frequency temperature coefficient in perovskite microwave dielectric ceramics is solved, and the preparation of high-performance ceramics is realized.

CN119118667APending Publication Date: 2024-12-13QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411277071.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art lacks relevant basis for the preparation of high-performance perovskite microwave dielectric ceramics, especially for non-eigen factors such as the influence of grain boundary number and trench size on the resonant frequency temperature coefficient is unclear.

Method used

By determining the relationship between the number of grain boundaries of the target object and the overall Gibbs free energy, the depth of the grain boundary trench and the Gibbs free energy of the grain boundary, and obtaining the object using the laser microscope Raman test method The phase composition distribution is determined to determine the optimal preparation process parameters so that the resonant frequency temperature coefficient tends to zero.

Benefits of technology

It provides a theoretical basis for the preparation of high-performance perovskite microwave dielectric ceramics, accurately controls the number of grain boundaries, groove size and phase composition, and designs microwave dielectric ceramics that meet actual needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118667A_ABST
    Figure CN119118667A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite microwave dielectric ceramic preparation method, system and device, a medium and a product, and relates to the field of electronic information functional material preparation, the method comprises the following steps: determining the relationship between the number of grain boundaries of a target object and the overall Gibbs free energy; determining the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy; testing composition and distribution of grain boundary and intracrystalline phases of the target object by adopting a laser micro-Raman testing method to obtain a laser micro-Raman spectrum; based on the relationship between the number of the grain boundaries and the overall Gibbs free energy, the relationship between the depth of the grain boundary grooves and the Gibbs free energy of the grain boundaries and the laser microscopic Raman spectrum, determining optimal preparation process parameters, so that the resonant frequency temperature coefficient of the target object tends to zero; and the perovskite microwave dielectric ceramic is prepared according to the optimal preparation process parameters. According to the preparation method disclosed by the invention, a basis is provided for preparing the high-performance perovskite microwave dielectric ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of preparation of electronic information functional materials, and in particular to a method, system, equipment, medium and product for preparing perovskite microwave dielectric ceramics. Background Art

[0002] Microwave dielectric ceramics refer to ceramics that are suitable as dielectric materials in microwave frequency band circuits and perform certain functions. They play many functions in the circuit, such as dielectric waveguide, dielectric isolation and dielectric resonance. They are widely used in resonators, filters, dielectric waveguides, dielectric substrates and dielectric antennas, etc. They are key materials for modern microwave communication technologies such as satellite communications, global satellite positioning systems, and 5G communications.

[0003] There are many microwave ceramic systems, among which microwave ceramics with perovskite structure can be widely used in 4G and even 5G communication base stations as key materials for preparing resonators and filters due to their advantages such as high dielectric constant, small dielectric loss and controllable resonant frequency temperature coefficient. With the large-scale construction of 5G communication base stations in my country, the market demand for perovskite structure microwave ceramics is also increasing day by day.

[0004] Titanate-aluminate MTiO3-RAlO3 (M: Ba, Sr, Ca; R: La, Nd, Sm) microwave ceramics are new microwave ceramics developed on the basis of titanate MTiO3 (M: Ba, Sr, Ca) with medium-high dielectric constant, high Q×f value and near-zero τf. 1-x Ti 1-x R x Al x O3 (R: La, Nd, Sm; CTRA for short) system ceramics have the advantages of low cost, moderate dielectric constant, high Q×f (Q: quality factor; f: resonant frequency) value and adjustable resonant frequency temperature coefficient. They are key materials for modern microwave communication technology.

[0005] The resonant frequency temperature coefficient (τf) is a parameter to measure the temperature stability of microwave dielectric ceramics. In actual use, the resonant frequency temperature coefficient of microwave components is required to be adjustable near zero. At present, the relevant research on the resonant frequency temperature coefficient of perovskite structure microwave dielectric ceramics at home and abroad mainly focuses on intrinsic factors such as crystal structure, chemical bond valence, bond energy, and most of the research has only obtained qualitative laws for specific systems; the influence mechanism of non-intrinsic factors, especially the number of grain boundaries, groove size and phase composition on τf is not clear.

[0006] Calcium titanate doped aluminate Ca1-xTi 1-x R x Al xThe research on O3 (CTRA) microwave dielectric ceramics mainly focuses on improving dielectric properties by doping with additives or changing process parameters. However, there are still few reports on the influence of non-intrinsic factors such as the number of grain boundaries and grain boundary grooves on the temperature coefficient of resonant frequency (τf) and its physical mechanism, which makes the preparation of high-performance perovskite microwave dielectric ceramics lack of relevant basis. Summary of the invention

[0007] The purpose of this application is to provide a method, system, equipment, medium and product for preparing perovskite microwave dielectric ceramics to solve the problem of lack of relevant basis for preparing high-performance perovskite microwave dielectric ceramics.

[0008] To achieve the above objectives, this application provides the following solutions:

[0009] In a first aspect, the present application provides a method for preparing a perovskite microwave dielectric ceramic, the method comprising:

[0010] Determining the relationship between the number of grain boundaries and the overall Gibbs free energy of a target object; the target object is a perovskite microwave dielectric ceramic;

[0011] Determine the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy;

[0012] The laser micro-Raman testing method is used to test the phase composition distribution of the target object to obtain a laser micro-Raman spectrum; the phase composition distribution includes: the composition and distribution of the grain boundary phase and the composition and distribution of the intracrystalline phase;

[0013] Based on the relationship between the number of grain boundaries and the overall Gibbs free energy, the relationship between the depth of the grain boundary grooves and the grain boundary Gibbs free energy, and laser micro-Raman spectroscopy, the optimal preparation process parameters are determined so that the resonant frequency temperature coefficient of the target object tends to zero; the optimal preparation process parameters are used as a basis for the preparation of perovskite microwave dielectric ceramics.

[0014] Optionally, the relationship between the number of grain boundaries of the target object and the overall Gibbs free energy is expressed as:

[0015] dG=σ b dA

[0016] Where G represents the overall Gibbs free energy; σ b represents grain boundary energy; A represents the number of grain boundaries.

[0017] Optionally, the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy specifically includes:

[0018] Based on the grain boundary Gibbs free energy, the grain surface energy and the grain boundary angle of the grain boundary groove of the target object, the relationship between the grain boundary Gibbs free energy, the grain surface energy and the grain boundary angle of the grain boundary groove is determined;

[0019] According to the surface geometric model of the grain boundary groove, the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove is determined;

[0020] Based on the relationship between the grain boundary Gibbs free energy, the grain surface energy and the grain boundary angle of the grain boundary groove and the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove, the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy is determined.

[0021] Optionally, the relationship between the grain boundary Gibbs free energy, the grain surface energy, and the grain boundary angle of the grain boundary groove is expressed as:

[0022] γ gb / γ sv =2cosθ / 2;

[0023] Among them, γ gb represents the grain boundary Gibbs free energy; γ sv represents the surface energy of the grain, and θ represents the grain boundary angle of the grain boundary groove.

[0024] Optionally, the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove is expressed as:

[0025]

[0026] Wherein, θ represents the grain boundary angle of the grain boundary groove; ω represents the width of the grain boundary groove; and d represents the depth of the grain boundary groove.

[0027] Optionally, the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy is expressed as:

[0028]

[0029] Among them, γ gb represents the grain boundary Gibbs free energy; γ sv represents the surface energy of the grain; ω represents the width of the grain boundary groove; d represents the depth of the grain boundary groove.

[0030] In a second aspect, the present application provides a perovskite microwave dielectric ceramic preparation system, the perovskite microwave dielectric ceramic preparation system is based on the perovskite microwave dielectric ceramic preparation method, and the perovskite microwave dielectric ceramic preparation system comprises:

[0031] A unit for determining the relationship between the number of grain boundaries and the overall Gibbs free energy, used to determine the relationship between the number of grain boundaries and the overall Gibbs free energy of a target object; the target object is a perovskite microwave dielectric ceramic;

[0032] A unit for determining the relationship between the depth of a grain boundary groove and the grain boundary Gibbs free energy, used to determine the relationship between the depth of a grain boundary groove of a target object and the grain boundary Gibbs free energy;

[0033] A laser micro-Raman spectrum determination unit is used to test the phase composition distribution of the target object using a laser micro-Raman test method to obtain a laser micro-Raman spectrum; the phase composition distribution includes: the composition and distribution of the grain boundary phase and the composition and distribution of the intracrystalline phase;

[0034] The optimal preparation process parameter determination unit is used to determine the optimal preparation process parameters based on the relationship between the number of grain boundaries and the overall Gibbs free energy, the relationship between the depth of the grain boundary grooves and the grain boundary Gibbs free energy, and the laser micro-Raman spectrum, so as to make the resonant frequency temperature coefficient of the target object approach zero; the optimal preparation process parameters are used as a basis for the preparation of perovskite microwave dielectric ceramics.

[0035] In a third aspect, the present application provides a computer device, comprising: a memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor executes the computer program to implement the steps of the method for preparing perovskite microwave dielectric ceramics described in any one of the above.

[0036] In a fourth aspect, the present application provides a computer-readable storage medium having a computer program stored thereon, which, when executed by a processor, implements the steps of the method for preparing the perovskite microwave dielectric ceramic described in any one of the above.

[0037] In a fifth aspect, the present application provides a computer program product, including a computer program, which, when executed by a processor, implements the steps of the method for preparing perovskite microwave dielectric ceramics described in any one of the above.

[0038] According to the specific embodiments provided in this application, this application discloses the following technical effects:

[0039] The present application provides a method, system, equipment, medium and product for preparing perovskite microwave dielectric ceramics. By exploring the physical model and correlation between the number of grain boundaries, grain boundary grooves and phase composition and the corresponding thermodynamic parameters, the influence of the grain boundary grooves and phase composition on the resonant frequency temperature coefficient of the perovskite microwave dielectric ceramics is explored, and then the high-performance perovskite microwave dielectric ceramics with specific grain boundary numbers, groove sizes and phase compositions are prepared in a targeted manner, providing a theoretical basis for the preparation of high-performance perovskite microwave dielectric ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 This is a schematic diagram of a process for preparing a perovskite microwave dielectric ceramic in one embodiment of the present application;

[0042] Figure 2 A schematic diagram of a geometric model of a grain boundary groove surface provided in an embodiment of the present application;

[0043] Figure 3 For Co 3+ Schematic diagram of laser micro-Raman test results of doped perovskite ceramics at the grain boundary;

[0044] Figure 4 A schematic diagram of peak shape fitting results of full spectrum fitting structure refinement of CTSA ceramics provided in another embodiment of the present application;

[0045] Figure 5 A schematic diagram of peak shape fitting results of full spectrum fitting structure refinement of CTNA ceramics provided in one embodiment of the present application;

[0046] Figure 6 A schematic diagram of peak shape fitting results of full spectrum fitting structure refinement of CTLA ceramics provided in one embodiment of the present application;

[0047] Figure 7 A schematic diagram of a three-dimensional cross-sectional view of a CTSA ceramic at different sintering temperatures provided in an embodiment of the present application;

[0048] Figure 8 A schematic diagram of a cross-sectional view of the three-dimensional morphology of a CTNA ceramic at different sintering temperatures provided in one embodiment of the present application;

[0049] Fig. 9 A schematic diagram of a three-dimensional cross-sectional view of a CTLA ceramic at different sintering temperatures provided in one embodiment of the present application;

[0050] Fig.10 A schematic diagram of τf, thermal expansion coefficient and unit cell polarizability of CTSA ceramics at different sintering temperatures provided in one embodiment of the present application;

[0051] Fig.11 A schematic diagram of τf, thermal expansion coefficient and unit cell polarizability of CTNA ceramics at different sintering temperatures provided in one embodiment of the present application;

[0052] Fig.12 A schematic diagram of τf, thermal expansion coefficient and unit cell polarizability of CTLA ceramics at different sintering temperatures provided in one embodiment of the present application;

[0053] Fig.13 A schematic diagram of the microstructure morphology of CTSA ceramics provided in one embodiment of the present application;

[0054] Fig.14 A schematic diagram of the microstructure morphology of CTNA ceramics provided in one embodiment of the present application;

[0055] Fig.15 A schematic diagram of the microstructure morphology of CTLA ceramics provided in one embodiment of the present application;

[0056] Fig.16 A schematic diagram of functional modules of a perovskite microwave dielectric ceramic preparation system provided in one embodiment of the present application;

[0057] Fig.17 A schematic diagram of the structure of a computer device provided in one embodiment of the present application.

[0058] Reference numerals:

[0059] Unit 1 for determining the relationship between the number of grain boundaries and the overall Gibbs free energy, unit 2 for determining the relationship between the depth of the grain boundary grooves and the grain boundary Gibbs free energy, unit 3 for determining the laser micro-Raman spectrum, and unit 4 for determining the optimal preparation process parameters. DETAILED DESCRIPTION

[0060] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0061] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0062] The raw materials used in the preparation of CTRA microwave ceramics are: calcium carbonate CaCO3, aluminum oxide Al2O3, cobalt oxide Co3O4, titanium dioxide TiO2, niobium oxide Nb2O5, lanthanum oxide La2O3, samarium oxide Sm2O3 and neodymium oxide Nd2O3. The CTRA microwave ceramic samples that meet the test requirements are prepared in the range of 1300-1600℃ using the traditional solid phase ceramic sintering process. The specific preparation process is: the raw materials are ball milled according to the predetermined ratio, mixed evenly, dried and pre-fired, and the green body after forming is sintered into dense ceramics through solid phase reaction at an appropriate temperature.

[0063] After grinding off 200-300um of the surface of the sintered ceramic sample, it was polished into a mirror surface and then tested by X-ray diffractometer XRD. As a bulk polycrystalline material, the grain boundaries of CTRA microwave ceramics exist in three dimensions in the ceramics, so the number of ceramic grain boundaries must be measured and counted from all directions in the plane and three dimensions; the grain boundary grooves are obtained by thermal corrosion, which reflects the Gibbs free energy of the ceramics, so white light interferometer and atomic force microscope AFM are used to measure and count the three-dimensional morphology of the ceramic surface grain boundary grooves; the phase composition and distribution of the grain boundaries and grains of CTRA microwave ceramics are explored. The doping modification or preparation process change of ceramics will cause the phase composition and distribution at the grain boundaries to change, which can be tested by high-resolution transmission electron microscopy-energy spectrometer HRTEM-EDS, scanning electron microscopy SEM-EDS or laser micro-Raman and other manual methods to analyze the obtained grain boundary phase composition and distribution. At the same time, the microwave dielectric properties and thermal expansion tests of ceramic samples are tested, and the relationship between grain boundaries, intracrystalline phase composition and thermodynamic parameters is established to understand the evolution of CTRA microwave ceramic microstructure morphology and dielectric properties.

[0064] In an exemplary embodiment, Figure 1 As shown, a method for preparing perovskite microwave dielectric ceramics is provided, and the method is executed by a computer device, and specifically can be executed by a computer device such as a terminal or a server alone, or can be executed by a terminal and a server together. In the embodiment of the present application, the method is applied to a server as an example for explanation, and includes the following steps S1 to S5. Among them:

[0065] Step S1, determining the relationship between the number of grain boundaries and the overall Gibbs free energy of a target object; the target object is a perovskite microwave dielectric ceramic.

[0066] Step S2, determining the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy.

[0067] Step S3, using a laser micro-Raman testing method to test the composition and distribution of the grain boundary and intracrystalline phase of the target object to obtain a laser micro-Raman spectrum.

[0068] Step S4, based on the relationship between the number of grain boundaries and the overall Gibbs free energy, the relationship between the depth of the grain boundary grooves and the grain boundary Gibbs free energy, and the laser micro-Raman spectrum, determine the optimal preparation process parameters so that the resonant frequency temperature coefficient of the target object tends to zero. The preparation process parameters include stoichiometric ratio, pre-firing temperature, expected sintering time, sintering temperature, holding time, and doping ratio.

[0069] Step S5, preparing perovskite microwave dielectric ceramics according to the optimal preparation process parameters.

[0070] By implementing the above steps S1 to S5, the physical model and correlation between the number of grain boundaries, grain boundary grooves and phase composition and the corresponding thermodynamic parameters are explored to explore their influence on the resonant frequency temperature coefficient of perovskite microwave dielectric ceramics, providing a theoretical basis for preparing high-performance perovskite microwave dielectric ceramics. By adopting the above steps S1 to S5, the number of grain boundaries, the size of grain boundary grooves and the phase composition and distribution of the ceramic can be accurately controlled, so as to design microwave dielectric ceramics that meet actual needs.

[0071] In another exemplary embodiment of the present application, the expression for the relationship between the number of grain boundaries of the target object and the overall Gibbs free energy in step S1 is:

[0072] d G=σ b dA (1)

[0073] Where G represents the overall Gibbs free energy; σ b represents grain boundary energy; A represents the number of grain boundaries.

[0074] Specifically, grain boundaries, as one of the microstructural features in ceramic materials, will affect the dielectric properties and temperature stability of the material, and an increase in the number of grain boundaries will usually lead to a decrease in grain size, thereby affecting the dielectric constant and loss of the material, and further affecting the resonant frequency temperature coefficient. However, the specific relationship may vary depending on the material system and preparation process. The CTRA ceramics prepared in this application are polycrystalline materials. The grain size of the ceramic corresponds to the number of grain boundaries. As a two-dimensional crystal defect, the entropy value of the free energy of the grain boundary is higher than that of the crystal. Therefore, the number of grain boundaries directly reflects the value of the overall Gibbs free energy of the ceramic itself. In polycrystalline materials, the overall Gibbs free energy of CTRA ceramics can be calculated by formula (2):

[0075] G=∑μ i n i +σ b A (2)

[0076] Among them, μ i represents the grain boundary chemical potential energy of the i-th component; n i represents the number of components i, σb represents the grain boundary energy (i.e., surface tension), and A represents the grain boundary area (i.e., the number of grain boundaries). Assuming that the pressure, external temperature, and material volume of the CTRA ceramic are constants, the change in free energy can be expressed as formula (1).

[0077] The relationship between the number of grain boundaries and the overall Gibbs free energy of the ceramic can be obtained from formula (1). It can be found that: under the premise that the grain boundary free energy remains unchanged, the number of grain boundaries and the overall Gibbs free energy are in a positive proportional relationship, that is, the more grain boundaries there are, the greater the overall Gibbs free energy of the ceramic. By exploring the influence of the number of grain boundaries of CTRA ceramics on the thermodynamic parameters of the ceramic through formula (1), the influence mechanism of the number of grain boundaries on the thermodynamic parameters can be obtained.

[0078] In another exemplary embodiment of the present application, determining the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy in step S2 specifically includes:

[0079] Step S21, based on the grain boundary Gibbs free energy, grain surface energy and grain boundary angle of the grain boundary groove of the target object, determine the relationship between the grain boundary Gibbs free energy, grain surface energy and grain boundary angle of the grain boundary groove. The expression for the relationship between the grain boundary Gibbs free energy, grain surface energy and grain boundary angle of the grain boundary groove is:

[0080] γ gb / γ sv =2cosθ / 2 (3)

[0081] Among them, γ gb represents the grain boundary Gibbs free energy; γ sv represents the surface energy of the grain, θ represents the grain boundary angle of the grain boundary groove, and the ratio of the grain boundary Gibbs free energy to the grain surface energy is determined by the grain boundary angle of the grain boundary groove.

[0082] Step S22, determining the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove according to the surface geometric model of the grain boundary groove. The expression for the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove is:

[0083]

[0084] Wherein, θ represents the grain boundary angle of the grain boundary groove; ω represents the width of the grain boundary groove; and d represents the depth of the grain boundary groove.

[0085] Step S23, based on the relationship between the grain boundary Gibbs free energy, the grain surface energy, and the grain boundary angle of the grain boundary groove, and the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove, determine the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy. The expression for the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy is:

[0086]

[0087] Among them, γ gb represents the grain boundary Gibbs free energy; γ sv represents the surface energy of the grain; ω represents the width of the grain boundary groove; d represents the depth of the grain boundary groove.

[0088] Specifically, the study of the ceramic grain boundary grooves shows that the average width ω of the grain boundary grooves of CTRA ceramics is nanometer-level, and the depth d is micrometer-level, which are of different orders of magnitude. In addition, the depth of the ceramic grain boundary grooves is consistent with the change law of the thermal expansion coefficient, but the width of the grain boundary grooves is almost unchanged, which shows that the grain boundary Gibbs free energy of the ceramic sample is determined by the depth of the ceramic grain boundary grooves, that is, the greater the depth of the grain boundary grooves, the greater the Gibbs free energy of the ceramic grain boundary. At the same time, the thermal expansion coefficient αL of the ceramic is explored, which shows that the αL of the ceramic is inversely proportional to the grain size, that is, the larger the ceramic grain size (the fewer the number of grain boundaries), the smaller the αL, and the αL of the ceramic determines the change of the resonant frequency temperature coefficient τf of the ceramic to a certain extent, so the growth of the ceramic grain size will cause the ceramic τf to decrease.

[0089] From the perspective of thermodynamics, a physical model of the influence of grain boundary grooves on thermodynamic parameters is established. Figure 2 As shown, Figure 2 This is a schematic diagram of the geometric model of the grain boundary groove surface. The basic definitions of the width ω, depth d and grain boundary angle θ of the grain boundary groove are given. The grain boundary grooves of ceramics can be tested by three-dimensional morphology such as white light interferometry and AFM. According to the relevant theories of grain boundary grooves of polycrystalline materials, the relationship between grain boundary grooves and ceramic thermodynamic parameters can be calculated.

[0090] Among them, according to Figure 2 , based on geometric knowledge, the trigonometric function expression formula (4) can be calculated to obtain the expression of the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove.

[0091] According to formula (3) and formula (4), the expression (5) of the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy is obtained.

[0092] When the grain free energy is a constant, the energy of the grain boundary is The relationship is directly proportional, that is, the greater the depth of the grain boundary groove, the greater the energy of the grain boundary, and the greater the impact on the dielectric properties of the ceramic. According to the relevant theory of grain boundary grooves in polycrystalline materials, the mechanism of the influence of grain boundary grooves on thermodynamic parameters can be obtained.

[0093] In another exemplary embodiment of the present application, in step S3, based on the study of ceramic grain boundary phases, it is found that since different phases have different thermal expansion characteristics and dielectric properties, the composition and distribution of the ceramic grain boundary phases will affect the τf of the ceramic. High-resolution laser micro-Raman can be used to test the composition and distribution of the ceramic grain boundary and intracrystalline phases, such as Figure 3 As shown, Figure 3 For Co 3+ The laser microscopic Raman test results of doped perovskite ceramics at the grain boundary provide a new method and means for analyzing the influence of grain boundary phase composition and distribution on ceramic τf. Among them, by comparing microscopic imaging with Raman scattering peak analysis, the phase composition of ceramic grain boundaries can be intuitively observed. Figure 3 The Raman spectrum of the blue part in the figure is compared with the spectral peaks of the other two colors. There is an additional characteristic peak of Co2O3 with a Raman shift of 202. Therefore, the blue part is the doped phase with good solid solution of Co2O3, while the red and green phases are the phases without Co2O3. 3+ The replaced CaTiO3 phase can also be seen to have the same peak position and present different peak area spectrum distributions, indicating that different crystal structures may exist in the ceramic. Therefore, the number of ceramic grain boundaries, grain boundaries, and intracrystalline phase composition can be tested with the help of high-resolution laser micro-Raman to establish the intrinsic relationship between the ceramic grain boundary and intracrystalline phase composition and thermodynamic parameters, and explore the influence mechanism of grain boundary and intracrystalline phase composition on ceramic τf.

[0094] In other words, the influence of non-intrinsic factors on thermodynamic parameters is explored, and the influence on τf is further explored. The results show that a reduction in the number of ceramic grain boundaries will cause a decrease in the thermal expansion coefficient, which in turn leads to a decrease in the ceramic τf. In addition, a reduction in the depth of the CTRA ceramic grain boundary grooves will also lead to a decrease in the Gibbs free energy of the ceramic grain boundaries, thereby causing a decrease in the ceramic τf. However, during the production process, it is impossible to accurately control the number of grain boundaries or the depth of the grooves. It can only be adjusted by adjusting the process parameters such as the sintering temperature and doping ratio of the ceramic, so that the number of grain boundaries and the number of grooves are small, thereby obtaining ceramics with excellent performance.

[0095] Beneficial effects of this application:

[0096] (1) Different from the previous experience-based preparation of microwave dielectric ceramics, the present application obtains the process theory that affects the number of ceramic grain boundaries, groove size, and phase composition by constructing a physical model and correlation between the number of grain boundaries, grain boundary grooves, phase composition and distribution, and the corresponding thermodynamic parameters, and then directional preparation of high-performance microwave dielectric ceramics with a specific number of grain boundaries, groove size, phase composition and distribution.

[0097] (2) Different from the previous research on the temperature coefficient of resonant frequency by taking intrinsic factors such as crystal structure as the main contradiction, this application takes the number of grain boundaries, grain boundary grooves, phase composition and distribution, etc. that affect thermodynamic parameters as the main research objects from a thermodynamic perspective, explores the correlation calculation process between the number of grain boundaries, groove size, phase composition, distribution and thermodynamic parameters, constructs a geometric model of the influence of the number of grain boundaries, grain boundary grooves, phase composition and distribution on τf, and reveals the influence mechanism of thermodynamic parameters on τf of CTRA microwave dielectric ceramics.

[0098] Three groups of CTRA ceramics are prepared below to explore the influence mechanism of thermodynamic parameters on τf of CTRA microwave dielectric ceramics revealed by the preparation method of perovskite microwave dielectric ceramics in this application. The specific preparation process is as follows:

[0099] 1) Experiment: Using Ca 0.66 Ti 0.66 R 0.34 Al 0.34 Conventional solid-phase sintering process of O3-based ceramics: First, the stoichiometric ratio of the ceramic sample is calculated, and the oxide or carbonate with higher purity is selected. After ball milling, the slurry is dried and the powder is made, and then the ball milling and drying are performed again. Polyvinyl alcohol (PVA) is added, and the green body is formed after granulation, and then sintered.

[0100] 2) Thermal expansion meter test: The thermal expansion meter can determine the sintering process and test the thermal expansion coefficient respectively. The process of determining the sintering process is: first press the ceramic green body into a φ8mm×10mm cylinder, then put it into the DIL402PC thermal expansion meter to determine the relevant sintering process in the range of 25℃~1600℃, and the heating rate is 2℃ / min. The process of testing the thermal expansion coefficient of the ceramic sample is: first press the ceramic green body into a φ8mm×10mm cylinder, then put it into a high-temperature furnace and sinter it using the sintering process of the ceramic sample with the same component, and then use the DIL402PC thermal expansion meter to test the thermal expansion coefficient of the sintered cylinder at 25℃~200℃, and the heating rate is 2℃ / min. Repeat the test three times for each sample, and finally take the average value of the test.

[0101] 3) Phase analysis: XRD data were measured by Bruker AXSD8-Advance X-ray diffractometer, wherein the acceleration voltage was 30 kV, the current was 50 mA, the step scanning speed was 5° / min, the step length was 0.02°, and the scanning 2θ angle range was 10° to 80°.

[0102] 4) Microstructure analysis: First, the ceramic sample was surface ground and polished using a UNIPOL-802 precision grinding and polishing machine, and then subjected to high temperature thermal corrosion treatment. The microstructure of the ceramic was observed using a Hitachi SU8010 scanning electron microscope. The elemental analysis of the micro-region of the ceramic microstructure was obtained using an EDAX GENESIS spectrometer. The grain size of the ceramic microstructure was calculated using grain analysis software.

[0103] 5) Profile surface morphology analysis: First, the ceramic sample was ground and polished by UNIPOL-802 precision grinding and polishing machine, and then subjected to high temperature annealing and thermal corrosion treatment. The three-dimensional surface morphology of the polished sample was observed by Contour GT-K white light interferometer.

[0104] Finally, three groups of CTRA ceramics were obtained, among which the first group: CTSA ceramics, the dielectric performance parameters were: εr = 42.19, Q×f = 43620.74 GHz, τf = 4.99 ppm / ℃; the second group: CTNA ceramics, the dielectric performance parameters were: εr = 44.93, Q×f = 41292.71 GHz, τf = 7.79 ppm / ℃; the third group: CTLA ceramics, the dielectric performance parameters were: εr = 47.64, Q×f = 38389.57 GHz, τf = 9.92 ppm / ℃.

[0105] The peak shape fitting results of the full spectrum fitting and structure refinement of three groups of CTRA ceramics are shown in the figure. Figure 4-Figure 6 As shown, it can be concluded that in the ceramic unit cell, the proportion of ions occupying the A position, the proportion of ions occupying the B position, and the O ions coordinated with the two cations at the A and B positions are 2- The ratio of ions is 0.66:0.34, which is consistent with the stoichiometric ratio in the chemical formula, indicating that a complete solid solution structure has been formed.

[0106] Schematic diagram of the three-dimensional cross-section of the three groups of CTRA ceramics at different sintering temperatures Figure 7-Figure 9 As shown by Figure 7-Figure 9It can be seen that when the three-dimensional morphology cross-section of the ceramic is at 1300℃~1400℃, the roughness of the cross-section is relatively large, the number of grain boundary grooves is relatively large, and the depth of the grain boundary grooves is relatively large; at 1450℃~1500℃, the roughness of the cross-section is relatively small, the number of grain boundary grooves decreases accordingly, and the depth of the grain boundary grooves is relatively small; at 1550℃~1600℃, the roughness of the cross-section increases, and although the number of grain boundary grooves does not change, the depth of the grain boundary grooves increases.

[0107] Schematic diagram of τf, thermal expansion coefficient and unit cell polarizability of three groups of CTRA ceramics at different sintering temperatures. Figure 10-12 As shown, it can be seen that the change law of the resonant frequency temperature coefficient (τf) of the three groups of CTRA ceramics is the same, and they all show a trend of decreasing with the increase of sintering temperature, while the unit cell polarizability of the ceramics has almost no change at different sintering temperatures. This is because the crystal structure of the ceramics does not change much at different sintering temperatures; and the resonant frequency temperature coefficient (τf) of the ceramics is directly proportional to the thermal expansion coefficient (αL) of the ceramics, so the change law shown in the figure is obtained. Therefore, according to the previous research results on the microstructure morphology of ceramics, the thermal expansion coefficient (αL) of ceramics is inversely proportional to the grain size of the ceramics, that is, the larger the grain size of the ceramics (that is, the fewer the number of grain boundaries), the smaller the thermal expansion coefficient, and the thermal expansion coefficient (αL) of the ceramics determines the change of the resonant frequency temperature coefficient (τf) of the ceramics to a certain extent, so the growth of the ceramic grain size will cause the reduction of the resonant frequency temperature coefficient (τf) of the ceramics to a certain extent.

[0108] Schematic diagram of the microstructure of three groups of CTRA ceramics Figure 13-Figure 15 As shown, it can be concluded that the three components of CTRA ceramics can be kept at 1450℃ for 4h to obtain ceramic samples with excellent performance. Observation of their microstructural morphology shows that the samples have high density, obvious grain boundaries, uniform ceramic grain size, and an average grain size of 6.2-7.2μm. There is no particularly obvious abnormal grain growth, and no obvious second phase is observed.

[0109] Ultimately, the excellent dielectric properties enable these three groups of CTRA ceramics to be used as matrix materials in wireless communication devices.

[0110] Based on the same inventive concept, the embodiment of the present application also provides a perovskite microwave dielectric ceramic preparation system for implementing the above-mentioned perovskite microwave dielectric ceramic preparation method. The implementation solution provided by the system to solve the problem is similar to the implementation solution recorded in the above-mentioned method, so the specific limitations in one or more perovskite microwave dielectric ceramic preparation system embodiments provided below can refer to the limitations of the perovskite microwave dielectric ceramic preparation method above, and will not be repeated here.

[0111] In an exemplary embodiment, Fig.16 As shown, a perovskite microwave dielectric ceramic preparation system is provided, including: a unit 1 for determining the relationship between the number of grain boundaries and the overall Gibbs free energy, a unit 2 for determining the relationship between the depth of the grain boundary grooves and the grain boundary Gibbs free energy, a laser micro-Raman spectrum determination unit 3 and an optimal preparation process parameter determination unit 4.

[0112] The relationship determination unit 1 between the number of grain boundaries and the overall Gibbs free energy is used to determine the relationship between the number of grain boundaries and the overall Gibbs free energy of a target object; the target object is a perovskite microwave dielectric ceramic.

[0113] The relationship determination unit 2 between the depth of the grain boundary groove and the grain boundary Gibbs free energy is used to determine the relationship between the depth of the grain boundary groove and the grain boundary Gibbs free energy of the target object.

[0114] The laser micro-Raman spectrum determination unit 3 is used to test the composition and distribution of the grain boundary and the intracrystalline phase of the target object by using the laser micro-Raman test method to obtain the laser micro-Raman spectrum.

[0115] The optimal preparation process parameter determination unit 4 is used to determine the optimal preparation process parameters based on the relationship between the number of grain boundaries and the overall Gibbs free energy, the relationship between the depth of the grain boundary grooves and the grain boundary Gibbs free energy, and the laser micro-Raman spectrum, so as to make the resonant frequency temperature coefficient of the target object approach zero; and prepare perovskite microwave dielectric ceramics using the optimal preparation process parameters.

[0116] In an exemplary embodiment, a computer device is provided. The computer device may be a server or a terminal. The internal structure diagram thereof may be as follows: Fig.17 As shown. The computer device includes a processor, a memory, an input / output interface (Input / Output, referred to as I / O) and a communication interface. Wherein, the processor, the memory and the input / output interface are connected through a system bus, and the communication interface is connected to the system bus through the input / output interface. Wherein, the processor of the computer device is used to provide computing and control capabilities. The memory of the computer device includes a non-volatile storage medium and an internal memory. The non-volatile storage medium stores an operating system, a computer program and a database. The internal memory provides an environment for the operation of the operating system and the computer program in the non-volatile storage medium. The input / output interface of the computer device is used to exchange information between the processor and an external device. The communication interface of the computer device is used to communicate with an external terminal through a network connection. When the computer program is executed by the processor, a method for preparing a perovskite microwave dielectric ceramic is implemented.

[0117] Those skilled in the art will understand that Fig.17 The structure shown in the figure is only a block diagram of a part of the structure related to the solution of the present application, and does not constitute a limitation on the computer device to which the solution of the present application is applied. The specific computer device may include more or fewer components than those shown in the figure, or combine certain components, or have a different arrangement of components. In an exemplary embodiment, a computer device is provided, including a memory and a processor, wherein a computer program is stored in the memory, and the processor implements the steps in the above-mentioned method embodiments when executing the computer program.

[0118] In an exemplary embodiment, a computer-readable storage medium is provided, storing a computer program, and when the computer program is executed by a processor, the steps in the above method embodiments are implemented.

[0119] In an exemplary embodiment, a computer program product is provided, including a computer program, and when the computer program is executed by a processor, the steps in the above method embodiments are implemented.

[0120] It should be noted that the user information (including but not limited to user device information, user personal information, etc.) and data (including but not limited to data used for analysis, stored data, displayed data, etc.) involved in this application are all information and data authorized by the user or fully authorized by all parties, and the collection, use and processing of relevant data must comply with relevant regulations.

[0121] Those of ordinary skill in the art can understand that all or part of the processes in the above-mentioned embodiment methods can be completed by instructing the relevant hardware through a computer program, and the computer program can be stored in a non-volatile computer-readable storage medium. When the computer program is executed, it can include the processes of the embodiments of the above-mentioned methods. Among them, any reference to the memory, database or other medium used in the embodiments provided in the present application can include at least one of non-volatile and volatile memory. Non-volatile memory can include read-only memory (ROM), magnetic tape, floppy disk, flash memory, optical memory, high-density embedded non-volatile memory, resistive random access memory (ReRAM), magnetic random access memory (MRAM), ferroelectric random access memory (FRAM), phase change memory (PCM), graphene memory, etc. Volatile memory can include random access memory (RAM) or external cache memory, etc. By way of illustration and not limitation, RAM may be in various forms, such as static random access memory (SRAM) or dynamic random access memory (DRAM).

[0122] The database involved in each embodiment provided in this application may include at least one of a relational database and a non-relational database. The non-relational database may include a distributed database based on blockchain, etc., but is not limited thereto. The processor involved in each embodiment provided in this application may be a general-purpose processor, a central processing unit, a graphics processor, a digital signal processor, a programmable logic device, a data processing logic device based on quantum computing, etc., but is not limited thereto.

[0123] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0124] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and core ideas of this application. At the same time, for those skilled in the art, according to the ideas of this application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting this application.

Claims

1. A method for preparing perovskite microwave dielectric ceramics, It is characterized in that The method for preparing the perovskite microwave dielectric ceramic comprises: Determining the relationship between the number of grain boundaries and the overall Gibbs free energy of a target object; the target object is a perovskite microwave dielectric ceramic; Determine the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy; The laser micro-Raman testing method is used to test the phase composition distribution of the target object to obtain a laser micro-Raman spectrum; the phase composition distribution includes: the composition and distribution of the grain boundary phase and the composition and distribution of the intracrystalline phase; Based on the relationship between the number of grain boundaries and the overall Gibbs free energy, the relationship between the depth of the grain boundary grooves and the grain boundary Gibbs free energy, and laser micro-Raman spectroscopy, the optimal preparation process parameters are determined so that the resonant frequency temperature coefficient of the target object tends to zero; the optimal preparation process parameters are used as a basis for the preparation of perovskite microwave dielectric ceramics.

2. The method for preparing perovskite microwave dielectric ceramics according to claim 1, It is characterized in that The expression for the relationship between the number of grain boundaries and the overall Gibbs free energy of the target object is: dG=σ b dA Where G represents the overall Gibbs free energy; σ b represents grain boundary energy; A represents the number of grain boundaries.

3. The method for preparing perovskite microwave dielectric ceramics according to claim 1, It is characterized in that The relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy specifically includes: Based on the grain boundary Gibbs free energy, the grain surface energy and the grain boundary angle of the grain boundary groove of the target object, the relationship between the grain boundary Gibbs free energy, the grain surface energy and the grain boundary angle of the grain boundary groove is determined; According to the surface geometric model of the grain boundary groove, the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove is determined; Based on the relationship between the grain boundary Gibbs free energy, the grain surface energy and the grain boundary angle of the grain boundary groove and the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove, the relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy is determined.

4. The method for preparing perovskite microwave dielectric ceramics according to claim 3, It is characterized in that The relationship between the grain boundary Gibbs free energy, the grain surface energy, and the grain boundary angle of the grain boundary groove is expressed as: c gb / c sv =2cosθ / 2; Among them, γ gb represents the grain boundary Gibbs free energy; γ sv represents the surface energy of the grain, and θ represents the grain boundary angle of the grain boundary groove.

5. The method for preparing perovskite microwave dielectric ceramics according to claim 3, It is characterized in that The expression for the relationship between the grain boundary angle of the grain boundary groove and the depth of the grain boundary groove is: Wherein, θ represents the grain boundary angle of the grain boundary groove; ω represents the width of the grain boundary groove; and d represents the depth of the grain boundary groove.

6. The method for preparing perovskite microwave dielectric ceramics according to claim 3, It is characterized in that The relationship between the depth of the grain boundary groove of the target object and the grain boundary Gibbs free energy is expressed as: Among them, γ gb represents the grain boundary Gibbs free energy; γ sv represents the surface energy of the grain; ω represents the width of the grain boundary groove; d represents the depth of the grain boundary groove.

7. A perovskite microwave dielectric ceramic preparation system, It is characterized in that The perovskite microwave dielectric ceramic preparation system is implemented based on the perovskite microwave dielectric ceramic preparation method according to any one of claims 1 to 6, and the perovskite microwave dielectric ceramic preparation system comprises: A unit for determining the relationship between the number of grain boundaries and the overall Gibbs free energy, used to determine the relationship between the number of grain boundaries and the overall Gibbs free energy of a target object; the target object is a perovskite microwave dielectric ceramic; A unit for determining the relationship between the depth of a grain boundary groove and the grain boundary Gibbs free energy, used to determine the relationship between the depth of a grain boundary groove of a target object and the grain boundary Gibbs free energy; A laser micro-Raman spectrum determination unit is used to test the phase composition distribution of the target object using a laser micro-Raman test method to obtain a laser micro-Raman spectrum; the phase composition distribution includes: the composition and distribution of the grain boundary phase and the composition and distribution of the intracrystalline phase; The optimal preparation process parameter determination unit is used to determine the optimal preparation process parameters based on the relationship between the number of grain boundaries and the overall Gibbs free energy, the relationship between the depth of the grain boundary grooves and the grain boundary Gibbs free energy, and the laser micro-Raman spectrum, so as to make the resonant frequency temperature coefficient of the target object approach zero; the optimal preparation process parameters are used as a basis for the preparation of perovskite microwave dielectric ceramics.

8. A computer device, include: A memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor executes the computer program to implement the method for preparing the perovskite microwave dielectric ceramics according to any one of claims 1 to 6.

9. A computer-readable storage medium having a computer program stored thereon, It is characterized in that When the computer program is executed by a processor, the method for preparing the perovskite microwave dielectric ceramic according to any one of claims 1 to 6 is implemented.

10. A computer program product comprising a computer program, It is characterized in that When the computer program is executed by a processor, the method for preparing the perovskite microwave dielectric ceramic according to any one of claims 1 to 6 is implemented.